An improved tabu-based vector optimal algorithm for design optimizations of electromagnetic devices - Yang, S. Y.; Cardoso, JR; Ho, S. L.; Ni, P. H.; Machado, J. M.; Lo, EWC (Institute of Electrical and Electronics Engineers (IEEE), 2004)
This paper introduces an improved tabu-based vector optimal algorithm for multiobjective optimal designs of electromagnetic devices. The improvements include a division of the entire search process, a new method for fitness assignment, a novel scheme for the generation and selection of neighborhood solutions, and so forth. Numerical results on a mathematical function and an engineering multiobjective design problem demonstrate that the proposed method can produce virtually the exact Pareto front, in both parameter and objective spaces, even though the iteration number used by it is only about 70% of that required by its ancestor.
Keywords: multiobjective optimization; nondominated sorting; Pareto solution; tabu search; vector optimization